Greco-Gauchos: National Regeneration and Fascist Hellenism in Leopoldo Lugones - Outes-León, Brais (Revista Canadiense de Estudios Hispánicos, 2025)
This study explores the centrality of Hellenism within the political evolution towards authoritarianism of Argentine intellectual Leopoldo Lugones (1874-1938). Starting with his vindication of the Hellenist filiation of Argentina in El payador (1916) as a foundational myth of national identity, this analysis shows how the discursive articulation of a Fascist Hellenism comes to full fruition in Estudios helénicos (1924) and Nuevos estudios helénicos (1928). By combining philology and political discourse, in these two volumes Lugones articulates a Fascist project of national regeneration that vindicates the masculine and militaristic values of Homeric epic heroism as antidote against liberal democracy.